Necropolítica Ecuatoriana: Crisis carcelaria 2021-2022 - Viejó Vintimilla, América Belén (2023)
This article is a compilation of the most critical events related to the prison crisis that Ecuador has gone through between 2021-2022. Thus, through the discourse analysis tool of journalistic notes and theoretical bases such as governmentality or self-control (Foucault) have opened the doors to understand the effects of public policies implemented by the state. In the same way, the social capital (Bourdieu and Putman) that the PPL have managed to achieve the entry of weapons, this being the biggest problem for the security of penitentiary centers and its social consequences.